Including a special section: issues from multimedia gaming technology - Raitt, David (The electronic library: the international journal for the application of technology in information environments, 2005)
Publishes selected papers from the 3rd International Conference on the Application and Development of Computer Games held in Hong Kong 26-27 April 2004
Keywords: Information theory; Library science